2022
DOI: 10.1002/brb3.2625
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal striatal hypoconnectivity predicts antipsychotic medication treatment response in first‐episode psychosis and unmedicated patients with schizophrenia

Abstract: Introduction:The dorsal striatum, comprised of the caudate and putamen, is implicated in the pathophysiology of psychosis spectrum disorders. Given the high concentration of dopamine receptors in the striatum, striatal dopamine imbalance is a likely cause in cortico-striatal dysconnectivity. There is great interest in understanding the relationship between striatal abnormalities in psychosis and antipsychotic treatment response, but few studies have considered differential involvement of the caudate and putame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…After screening and eligibility assessment 28 studies were included. In one study ( Nelson et al, 2022 ) we identified two distinct cohorts, which we subsequently referred to as Nelson 2022a and Nelson2022b in our study. A total of 952 patients were investigated of which 551 with FE psychosis, 220 with two or more episodes or chronic psychosis, and 181 patients with unknown state of disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening and eligibility assessment 28 studies were included. In one study ( Nelson et al, 2022 ) we identified two distinct cohorts, which we subsequently referred to as Nelson 2022a and Nelson2022b in our study. A total of 952 patients were investigated of which 551 with FE psychosis, 220 with two or more episodes or chronic psychosis, and 181 patients with unknown state of disease.…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics are shown in Table 1a , Table 1b , Table 1c . Q1) seventeen studies reported on baseline fMRI-FC and AP-R at follow-up ( Anticevic et al, 2015 , Blazer et al, 2022 , Cadena et al, 2019 , Deng et al, 2022 , Doucet et al, 2020 , Hadley et al, 2014 , Han et al, 2020 , Kraguljac et al, 2016 , Kraguljac et al, 2016 , Li et al, 2020 , Maximo et al, 2021 , Nelson et al, 2022 , Sarpal et al, 2016 , Wang et al, 2019 , Zhang et al, 2019 , Blessing et al, 2020 , Zong et al, 2019 ), Q2) eighteen studies investigated associations between changes in fMRI-FC characteristics before and after treatment related to AP-R ( Anticevic et al, 2015 , Blazer et al, 2022 , Cadena et al, 2019 , Chopra et al, 2021 , Deng et al, 2022 , Duan et al, 2020 , Hadley et al, 2014 , Hadley et al, 2016 , Han et al, 2020 , Kraguljac et al, 2016 , Li et al, 2016 , Li et al, 2020 , Liu et al, 2022 , Sarpal et al, 2015 , Shan et al, 2021 , Wang et al, 2019 , Blessing et al, 2020 , Zong et al, 2019 ), Q3) nine studies investigated the prediction of AP-R based on fMRI-FC ( Cao et al, 2018 , Li et al, 2020 , Li et al, 2020 , Liu et al, 2022 , Sarpal et al, 2016 , Shan et al, 2021 , Zhu et al, 2018 , Blessing et al, 2020 , Nejad et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross‐validation of resting state functional connectivity patterns predictive of treatment response in patients with different clinical characteristics and environments is important to test the stability of the predictor. Accordingly, striatal resting state functional connectivity was explored in two cohorts of patients scanned on different MRI platforms: a cohort of medication‐naïve first‐episode patients and a cohort of unmedicated patients with schizophrenia 261 . In both cohorts, striatal resting state functional connectivity was predictive of subsequent treatment response to antipsychotic medication.…”
Section: Fmri In Relation To Treatment: Response/resistance Mechanism...mentioning
confidence: 99%
“…Other functional networks have been studied in relation to their potential to predict antipsychotic treatment response. Functional connectivity of the DMN 262 has been investigated in the above mentioned two cohorts 261 . In both of them, resting state functional connectivity of the hippocampus, one of the principal regions of the DMN, was predictive of subsequent treatment response.…”
Section: Fmri In Relation To Treatment: Response/resistance Mechanism...mentioning
confidence: 99%